Degradation of polychlorinated biphenyls in aqueous solutions after UV-peroxide treatment: Focus on toxicity of effluent to primary producers - Yu, Dennis N. (Animo Repository, 2011)
The combination of UV irradiation and hydrogen peroxide (UV-H2O2) was shown to be effective in treating water spiked with 2,2',4,4',5,5'-hexachlorobipheny (PCB 153), reducing its concentration by as much as 98%. To test the toxicity of the effluent, bioassays involving three species of primary producers were performed. Results showed the effluent exerting an adverse effect on the algae Scenedesmus bijugatus and the duckweed Lemna paucicostata. On the other hand, exposure of the mungbean Vigna radiata to the effluent revealed mostly no statistically significant adverse effect or growth stimulation. This suggested that on an exposure period of 96h, higher forms of chlorophyll-bearing species such as plants are relatively unaffected by trace concentrations of PCBs and degradation products, while less differentiated species like algae and duckweeds are vulnerable. © 2011 Elsevier Inc.